The Influence of the Economic Situation on Employment and its Structure in the Central and Eastern European Countries - Mariusz Zielinski (Institute of Economic Research (IER), 2017)
The Central and Eastern European countries suffered from a decrease in professional activity and increases in unemployment, income inequality, and underemployment. In most of the countries in the region, it was decided to increase labour market flexibility, adopting a Western European model of labour market functioning. The effects of deregulation (flexibility increase) for the labour market depend to a great extent on the economic situation. The paper attempts to answer the question of the degree to which changes in the employment level and structure can be explained by changes in the economic situation. The article verified two hypotheses: 'the employment level reacts to changes in the economic situation; however, this reaction in the Central and Eastern European countries is more severe than the average reaction in the European Union' (H1) and 'changes in the economic situation decide to a greater extent the employment level in the groups experiencing discrimination (women, youngest and oldest people) more than for employees in general' (H2). The research encompassed 11 Central and Eastern European countries (Bulgaria, the Czech Republic, Estonia, Croatia, Latvia, Lithuania, Hungary, Poland, Romania, Slovenia and Slovakia) on the basis of statistical data published by Eurostat for the period of 2004 to 2015. Data analysis was performed using the correlation coefficient and coefficient of determination. In the majority of the examined countries, a statistically significant correlation occurs between changes in GDP and total employment level; furthermore, the influence of changes in GDP on the employment level is greater than the European Union's average. The data do not indicate discrimination against certain groups (women, young people, people in pre-retirement age), changes in the employment levels of the aforementioned groups are less dependent on the economic situation than the changes in total employment.
Keywords: E24; E32; J16; J21; J70; 330; economic growth; employment; discrimination on the labor market; Central and Eastern European countries; European Union